Bridging The Gap Between Maritime Education and Industry Needs: Enhancing Human Resource Development - Jaja Suparman; Imam Fahcruddin; April Gunawan Malau; Wardoyo Dwi Kurniawan; Muhammad Sayakfika; Geboy Geboy (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
This research explores the critical need for maritime vocational education to align more closely with the evolving demands of the maritime industry, particularly in the areas of technological integration, environmental compliance, and industry collaboration. By analyzing the qualitative perspectives of maritime professionals, educators, graduates, and senior government officers, the study identifies key gaps in the current educational framework. The findings highlight the moderate effectiveness of existing programs, with strengths in regulatory knowledge and industry-academia partnerships, but weaknesses in preparing students for advanced technological systems and practical environmental challenges. The study emphasizes the need for curriculum modernization, increased hands-on training, and deeper, long-term industry partnerships to equip future maritime professionals with the skills necessary to navigate a rapidly changing sector. Ultimately, this research provides actionable insights for improving the responsiveness and agility of maritime vocational schools, ensuring that graduates are better prepared for the technological, regulatory, and environmental challenges facing the maritime industry.